1992
DOI: 10.1111/j.1751-1097.1992.tb09594.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOPEROXIDATION OF CHOLESTEROL IN HOMOGENEOUS SOLUTION, ISOLATED MEMBRANES, AND CELLS: COMPARISON OF THE 5α‐ AND 6β‐HYDROPEROXIDES AS INDICATORS OF SINGLET OXYGEN INTERMEDIACY

Abstract: Singlet oxygen (1O2) can react with cholesterol (Ch) to give three possible ene-addition hydroperoxides: 3 beta-hydroxy-5 alpha-cholest-6-ene-5-hydroperoxide (5 alpha-OOH), 3 beta-hydroxycholest-4-ene-6 alpha-hydroperoxide (6 alpha-OOH), and 3 beta-hydroxycholest-4-ene-6 beta-hydroperoxide (6 beta-OOH). The rates of dye-sensitized photogeneration and also the fates of 5 alpha-OOH and 6 beta-OOH in membrane bilayers have been studied and compared. Irradiation of unilamellar [14C]Ch/phospholipid vesicles in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(58 citation statements)
references
References 24 publications
1
56
0
1
Order By: Relevance
“…The percentage of sterol photooxidation was estimated using Eq. (3) (Christodoulou et al, 2009), based on the ratio 4 -6α/β-hydroperoxides/ 6 -5α-hydroperoxides found in biological membranes (0.30) (Korytowski et al, 1992):…”
Section: -Sterolsmentioning
confidence: 99%
“…The percentage of sterol photooxidation was estimated using Eq. (3) (Christodoulou et al, 2009), based on the ratio 4 -6α/β-hydroperoxides/ 6 -5α-hydroperoxides found in biological membranes (0.30) (Korytowski et al, 1992):…”
Section: -Sterolsmentioning
confidence: 99%
“…D 4 -6a/6b-Hydroperoxides were selected as tracers of photooxidation of D 5 -sterols because of their high specificity and relative stability (Christodoulou et al 2009;Rontani et al 2009). These compounds were quantified after NaBH 4 reduction to the corresponding diols and the sterol photooxidation percentage was estimated with the following equation (Christodoulou et al 2009;Rontani et al 2009): Sterol photooxidation % 5 (D 4 -3b,6a/b-dihydroxysterol %) 3 (1 + 0.3)/ 0.3, on the basis of the ratio D 4 -6a/6b-hydroperoxides/D 6 -5a-hydroperoxides measured in biological membranes (0.30, Korytowski et al 1992).…”
Section: -Cismentioning
confidence: 99%
“…Colour deterioration and lipid oxidation may be linked, although the precise mechanisms are still unclear 16 . Furthermore, the oxidation of PUFA would induce cholesterol oxidation [17][18] . It is known that cholesterol oxidation products (COP) are clearly involved in the development of cardiovascular diseases 19 , and are also associated with the development of some biological effects like cytotoxicity, mutagenesis and carcinogenesis [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%